Social factors related to the quality of life among older adults in southwestern Poland - Antonina Kaczorowska; Małgorzata Kołodziej; Anna Sebastjan; Zofia Ignasiak (PLoS ONE, 2026)
Background The quality of life of older adults is closely linked to functioning in the living environment. This study aims to assess the quality of life of older adults in southwestern Poland and the social factors determining it. Methods This cross-sectional study included a voluntary sample of 1108 older adults aged 60‒90. The WHOQoL-BREF questionnaire was used to assess quality of life. Results The overall quality of life of the respondents (57%) was good. Men had a better quality of life in the psychological (69.0 ± 9.5 vs. 63.0 ± 6.5, p < 0.001) and environmental (69.0 ± 6.0 vs. 63.0 ± 9.5, p < 0.01) domains compared to women. In comparison, those living in a relationship had a better quality of life in the somatic (75.0 ± 9.0 vs. 69.0 ± 9.0, p = 0.034), social (75.0 ± 12.5 vs. 69.0 ± 9.5, p < 0.001), and environmental (69.0 ± 6.0 vs. 63.0 ± 9.5, p < 0.001) domains. Those with higher education had a better quality of life in the somatic (75.0 ± 6.0 vs. 69.0 ± 9.0 and 69.0 ± 9.0, p < 0.001), psychological (69.0 ± 6.5 vs. 63.0 ± 9.5 and 63.0 ± 6.5, p < 0.001), and environmental (69.0 ± 6.0 vs. 63.0 ± 9.5 and 63.0 ± 6.5, p < 0.001) domains compared to those with secondary and primary education. Respondents in good health had a better quality of life in all domains. Conclusions Good quality of life in older adults surveyed is determined by male gender, marital status in a relationship, higher education, good health ratings, and fewer chronic diseases. Our results can guide policymakers, highlighting the fact that good health, fewer chronic diseases, and higher education, translate into a better quality of life. Therefore, there should be improved access to education for all people. And good population health should be prioritized by decision-makers. Trial registration ISRCTN platform as 18225729; January 2021.